2019
DOI: 10.1002/rcs.2057
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of double versus triple button reconstruction techniques in patients with acromioclavicular joint dislocation

Abstract: Background: Although many techniques are used to treat the acromioclavicular (AC) joint dislocations, minimal invasive or arthroscopic coracoclavicular ligament reconstructions became popular recently. In this study, authors compared the biomechanical results of double versus triple button reconstruction techniques.Methods: Three-dimensional solid modeling of the shoulder girdle was carried out using virtual finite element modeling. AC joint dislocation was applied to the reference model, and these models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…We have demonstrated that acromioclavicular ligament augmentation repair combined with coracoclavicular ligament mini plate suspension xation is more stable than coracoclavicular ligament mini plate suspension xation alone. This result is consistent with the results of multiple nite element analysisrelated literatures (11)(12)(13). The nite element analysis study supported and validated our clinical research conclusions from three aspects: 1.…”
Section: Differences In the Selection Of Suspension Materials 4 Thesupporting
confidence: 90%
See 1 more Smart Citation
“…We have demonstrated that acromioclavicular ligament augmentation repair combined with coracoclavicular ligament mini plate suspension xation is more stable than coracoclavicular ligament mini plate suspension xation alone. This result is consistent with the results of multiple nite element analysisrelated literatures (11)(12)(13). The nite element analysis study supported and validated our clinical research conclusions from three aspects: 1.…”
Section: Differences In the Selection Of Suspension Materials 4 Thesupporting
confidence: 90%
“…At present, it remains controversy regarding the clinical application of Endobutton plate suspension surgery for the reduction of acromioclavicular dislocation. Through computer simulation of nite element analysis combined with biomechanical research, many scholars consider that additional augmentation suture repair of acromioclavicular ligament after reconstruction of coracoclavicular ligament can signi cantly improve the postoperative posterior displacement and rotation stability of acromioclavicular joint (11)(12)(13). However, some researchers carried out biomechanical analysis of cadaveric specimens simulating surgically treated acromioclavicular joint dislocation, and found that the effect of an additional acromioclavicular cerclage on the stability of acromioclavicular joint seemed to be negligible (14).…”
Section: Discussionmentioning
confidence: 99%
“…Ti6Al4V, the most common material properties, was chosen for K‐wire, intramedullary screw and tension band. The mechanical properties of the materials are shown in Table 1 21–25 …”
Section: Methodsmentioning
confidence: 99%
“…However, none of the groups in this study reached the ultimate load reported in the literature. This could be due to the bone-ligament-bone structure includes the properties of the clavicle and coracoid, and the clavicle stiffness would be reduced by 40% after dislocation [36][37][38][39] .…”
Section: Load Testingmentioning
confidence: 99%